2010
DOI: 10.1002/jts.20434
|View full text |Cite
|
Sign up to set email alerts
|

The impact of reported direct and indirect killing on mental health symptoms in Iraq war veterans

Abstract: This study examined the mental health impact of reported direct and indirect killing among 2,797 U.S. soldiers returning from Operation Iraqi Freedom. Data were collected as part of a postdeployment screening program at a large Army medical facility. Overall, 40% of soldiers reported killing or being responsible for killing during their deployment. Even after controlling for combat exposure, killing was a significant predictor of posttraumatic disorder (PTSD) symptoms, alcohol abuse, anger, and relationship pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
186
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 272 publications
(210 citation statements)
references
References 12 publications
19
186
2
3
Order By: Relevance
“…Exposure to combat on deployments to Iraq and Afghanistan has been linked with subsequent symptoms of PTSD [27,90,121,137]. Combat roles involve exposure to a variety of hazards with the potential to traumatise.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Exposure to combat on deployments to Iraq and Afghanistan has been linked with subsequent symptoms of PTSD [27,90,121,137]. Combat roles involve exposure to a variety of hazards with the potential to traumatise.…”
Section: Discussionmentioning
confidence: 99%
“…Combat roles involve exposure to a variety of hazards with the potential to traumatise. In particular, witnessing dead bodies [90,137], discharging a weapon in combat [90] and direct or indirect killing [121], have been shown to be strong predictors of PTSD in studies involving US personnel. Studies have also found that combat exposure is associated with alcohol misuse [95,104,121,188].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations